RANCANG BANGUN APLIKASI E-LEARNING PERGURUAN TINGGI DENGAN PEMODELAN BERBASIS UNIFIED MODELING LANGUAGE - Kamal, Angelina Gabriella; Wahyono, Teguh (Fakultas Teknologi Informasi, Universitas Kristen Satya Wacana, 2024)
Distance learning has become a supporting tool in education in the digital era. Improving the quality of education requires changing new, more efficient learning methods by designing E-Learning applications for learning media. The Manado State Christian Institute already has an Information System platform which aims to facilitate student registration and administration. To improve the quality of education, an E-Learning application is needed. The aim of this research is to design an E-Learning application as a distance learning platform that facilitates communication between students and lecturers in accessing material, assignments, challenges and exams. System design is carried out using Unified Modeling Language (UML) based modeling. Based on the results of usability testing, a score of 95.2% was obtained, which means that the E-Learning application is very good to use based on the experience of 5 respondents representing the Manado State Christian Institute.